2022
DOI: 10.1021/acsbiomaterials.2c00456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Electric Fields on Mechanical Properties and Microstructure of Ex Vivo Porcine Brain Tissues

Abstract: Electrotherapy plays a crucial role in regulating neuronal activity. Nevertheless, the relevant therapeutic mechanisms are still unclear; thus, the effects of electric fields on brain tissue's mechanical properties and microstructure need to be explored. In this study, focusing on the changes in mechanical properties and microstructure of ex vivo porcine brain tissues under different types of electric fields, directional and alternating electric fields (frequencies of 5, 20, 50, and 80 Hz, respectively) integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Data on load, displacement, and time were collected during the indentation and relaxation phases. Previous studies had demonstrated the suitability of Sneddon’s solution for soft biological tissues . The average shear modulus was calculated by substituting the force and displacement data from the loading phase into Sneddon’s solution …”
Section: Methodsmentioning
confidence: 99%
“…Data on load, displacement, and time were collected during the indentation and relaxation phases. Previous studies had demonstrated the suitability of Sneddon’s solution for soft biological tissues . The average shear modulus was calculated by substituting the force and displacement data from the loading phase into Sneddon’s solution …”
Section: Methodsmentioning
confidence: 99%